Socio-Economic Conditions Of Brick Kiln Workers In India - Nupur Rajvanshi (Elementary Education Online, 2023)
Construction activity is an integral part of the country’s infrastructure and industrial development. With the advent of new real estate projects in the form of malls, corporate offices, hospitals, schools, townships, highways, railways, airports, high rise apartments and commercial buildings, construction material is in great demand. Hence manufacturing units or brick kilns are in huge number in the western belt of Uttar Pradesh especially Baghpat, Muzaffarnagar and villages surrounding Meerut. Workers who are from the poor strata of our society especially the villagers prefer working in these kilns. Although the government of India, Ministry of Labour and Employment has declared ‘Pradhan Mantri Shram Yogi Maan-dhan Yojana for workers who work in unorganised sector’ but unfortunately these workers are absolutely clueless about these schemes and how to avail their benefits. Hence workers of this unorganised sector remain one of the most overlooked and vulnerable lot. Working and living conditions are quite harsh for them. As workers usually live within the kiln, they are exposed to hazardous substances such as burnt plastic, dust and arsenic. Labourers, including children get injured quite often at work. The average working hours are10-12 hours and majority of children do not attend school or have any play time whatsoever. The accommodation is usually overcrowded and uncomfortable, commonly with several families living together in one single room and outdoor toilets. Violence against workers, including beatings and abductions of family members, is quite common, especially when labourers seek help. Women are also particularly vulnerable to abuse and sexual harassment. To study the socio-economic conditions of these brick kiln workers, 228 workers were picked as sample from western belt of Uttar Pradesh especially from kilns of Meerut, Muzaffarnagar and Baghpat on random basis. Data was gathered through direct open ended and closed ended questionnaire and structured interview where demographic details were gathered along with the socio economic issues faced by the workers. Statistical Package for Social Sciences was used for the analysis followed by relevant suggestions which should be implemented thereof.